Prevalence of Metabolic Syndrome in Patients with Chronic Kidney Disease: A Hospital Based Cross-Sectional Study - Kanwal, Kanza; Abbasi, Muhammad Sajid Rafiq; Sultan, Khawar; Butt, Ghias; Ashraf, Muhammad Umer (Pakistan Journal of Kidney Diseases, 2025)
Chronic kidney disease (CKD) is an emerging health problem globally and metabolic syndrome is present in about one third of patients with CKD. Objective: To determine the frequency of metabolic syndrome in patients presenting with chronic kidney disease. Methods: We performed a single-center, descriptive cross sectional trial to assess the frequency of metabolic syndrome in patients presenting with CKD. 150 patients of both genders, age 20-40 years, with a diagnosis of CKD stage 3-5 regardless of dialysis were included in this study. Results: Mean age of the patients in the study was 28.10 + 12.46 years. The average weight of study patients was 63.5 + 5.8 (52-76) kilograms. Among 150 patients with CKD, 112 (75%) patients had no metabolic syndrome while half of patients of age range of range of 31-40 years had metabolic syndrome. In male had more metabolic syndrome compared to females. Patients with higher education and economic status were more likely to have metabolic syndrome and was more common among patients undergoing dialysis. Conclusions: Metabolic syndrome is common in patients presenting with CKD that may pose a higher morbidity .